Desenvolvimento de um carregador de baterias com aplicação em veículos elétricos envolvendo um conversor CA/CC controlado - Reis, Christian Struzik dos (2023)
The impending environmental issues and growing concerns about global energy crises are driving the need for new opportunities and technologies that can meet the significantly increased demand for cleaner and more sustainable energy systems. In the transportation sector, the current scenario of electric vehicles has stood out as an advantageous solution in terms of economic and environmental impacts. On the other hand, the use of these vehicles brings a challenge to the electrical grid because of the increase in demand linked to the need to charge the batteries. From the user’s point of view, charging also leads to the need to use different types of charging points, whether they are residential, public, or emergency. This work aims to study and develop a portable battery charger for electric vehicles, which would provide the user with greater ease of charging in an emergency condition. Considering applications involving electric cars, a controlled AC/DC converter is developed to perform the charging in an efficient way, considering power factor correction (PFC). To develop the battery charger, a power circuit will be designed capable of performing AC/DC conversion, followed by a second DC/DC conversion stage, with a Boost topology. Then, this circuit is analyzed mathematically in order to determine a control system, where computer simulations are carried out in order to validate the charger developed. In addition, a prototype of the charger is designed and dimensioned, which will be implemented experimentally in order to validate the design.